Delayed plant genetic responses to forest edge dynamics and their conservation implications - Lore Hostens; Christophe Metsu; Elissar Alam; Kasper Van Acker; Gerrit Peeters; Sander de Beer; Yannick Gansemans; Eugenija Kupcinskiene; Lina Jociene; Edvina Krokaite‐Kudakiene; Jolina Paulssen; Leonie Mazalla; et al. (Conservation Biology, 2026)
Understanding genetic responses to forest dynamics is essential for predicting the long‐term viability of understory plant populations and for developing effective conservation strategies. We investigated genetic extinction debt and colonization credit in broad‐leaved enchanter's nightshade ( Circaea lutetiana ), a clonal forest understory species, across its European range. Using pooled genotype‐by‐sequencing data from 40 forest edge and core populations, we examined to what extent population size, latitude, and historical changes in forest configuration may predict genetic diversity. Historical forest configuration profoundly shaped present‐day genetic diversity. Long‐established forest edge populations exhibited significantly reduced allelic richness (−9%) compared with core populations, indicating the partial payoff of a genetic extinction debt. In contrast, populations from recently established forest edges maintained allelic richness similar to core populations, suggesting delayed population genetic responses to land‐use changes. Finally, populations established in areas that were afforested during the past 250 years exhibited lower allelic richness (−10%) than historical forest core populations, indicating a delay in genetic recovery and thus a potential genetic colonization credit. Our results highlight that C. lutetiana populations are not at equilibrium with the current forest configuration, underscoring the role of lagged genetic responses across very long periods. Population size, and to a lesser extent connectivity, further mediated genetic diversity, with smaller, isolated populations being particularly vulnerable to genetic erosion. Given the limited research on delayed evolution in forest understory species, our results improve understanding of extinction risk dynamics and underscore the need for history‐informed restoration efforts.